Original growth mechanism for ultra-stable dendrite-free potassium metal electrode. (August 2019) - Li, Yuqian; Zhang, Liyuan; Liu, Sufu; Wang, Xiuli; Xie, Dong; Xia, Xinhui; Gu, Changdong; Tu, Jiangping
Abstract: Dendritic growth is relevant to the enrichment of local space charge, which largely resulting from weak connection between the deposited potassium metal and substrate. Here we illustrate the original growth mechanism of K metal by combining the tested over potential, the calculation of Gibbs free energies of K metal nucleate-grow on different substrates and Simulation models of electric field values . This mechanism suggests NiO nanoparticles as induced nuclear sites are implanted in puffed millet (PM) and can form well-knit root structures for large volume potassium metal deposition. Depending on this novel design, the PM/NiO/K electrode exhibits tiny voltage hysteresis in symmetric cells and the full battery (Potassium Prussian blue as cathode) reveals improved electrochemical performance. This work proposes a fabrication to achieve stable high-energy density anodes and suggests that the initial nucleation process is a crucial factor of dendritic growth. Graphical abstract: Original growth model of K metal on different substrates was established by combining the tested over potential, the calculation of Gibbs free energies of K metal nucleate-grow on different substrate and Simulation models of electric field values. Ultra-stable dendrite free Potassium metal electrodes were realized guiding by this mechanism.Image 1 Highlights: Original growth model of K metal on different substrates is establish. Elucidating the key role of NiO in K nucleation and growth process. The mass loading content of K metal in PM/NiO/K electrodes can reach 99.1 wt %. PM/NiO/K electrodes exhibit excellent structure stability and outstanding electrochemical properties.